The Invasion of the Dutch East Indies : Compiled by The War History Office of the National Defense College of Japan - Remmelink, Willem G. J., 1947-; Remmelink, Willem G. J., 1947- (Book collections on Project MUSE., 2015)
Between 1966 and 1980, the War History Office of the National Defense College of Japan published the 102-volume Senshi Sōsho (War History Series). These volumes give a detailed account of the operations of the Imperial Japanese Army and the Imperial Japanese Navy during the Second World War. This book, vol. 3 of the series, describes in depth the campaign to gain control over the Indonesian archipelago. (copyright: the Corts Foundation).